Diversity and the role of yeast in spontaneous cocoa bean fermentation from Southeast Sulawesi, Indonesia - JAMILI JAMILI; NUR ARFA YANTI; PRIMA ENDANG SUSILOWATI (Biodiversitas Journal of Biological Diversity, 2016)
Jamili, Yanti NA, Susilowati PE. 2016. Diversity and the role of yeast in spontaneous cocoa bean fermentation from Southeast Sulawesi, Indonesia. Biodiversitas 17: 90-95. Yeast is one of the microbial group which is role in the process of cocoa spontaneously fermentation. The objective of this study was to determinate and to know the diversity of yeast that role on cocoa bean fermentation. Yeast was isolated by pour plate method from cocoa bean that was naturally fermented by a cocoa farmer in Kolaka District, Southeast Sulawesi using yeast mannitol agar (YMA) media. Yeast was characterized and identified using phenotypic characters based on numeric-phenetic analysis. Yeast isolates applied to cocoa bean to determine its role in cocoa bean fermentation. The result was obtained seven isolates the dominant yeast during cocoa bean fermentation in Kolaka District, Southeast Sulawesi. The result of numerical-phenetic analysis based on phenotypic characters to seven yeast isolates showed that 1 isolates (Klk1) identical with Candida krusei. Three isolates (Klk4, Klk5 and Klk7) identical with Candida tropicalis, one isolate (Klk2) identical with Saccharomycopsis fibuligera, one isolate (Klk3) identical with Kloeckera sp. and one isolate (Klk6) identical with Saccharomyces cerevisiae. The result also showed that fermentation of cocoa with seeding of yeast inoculums served to increase the quality of cocoa beans than spontaneous fermentation. Therefore, the seven yeast isolates potentially be used as an inoculum to improve the cocoa quality.